Vicarious Learning: How Entrepreneurs Enhance a Firm’s International Competitiveness Through Learning From Interlocking Director Network Partners - Xie, Zaiyang; Lin, Runhui; Wang, Jie; Hu, Weiwei; Miao, Ling (Frontiers in Psychology, 2020)
Applying the lens of entrepreneurial psychology, this paper examines vicarious learning as an approach that entrepreneurs can use to overcome external uncertainty of overseas investments by accumulating international know-how and experience through interlocking director connections with other experienced companies. Through the analysis of a sample of Chinese companies, our findings suggest that entrepreneurs obtaining foreign experience from interlocking partners can significantly promote their firm’s international growth when investing in the same country, and that this positive effect is significant in relation to both first-degree and second-degree connections. We further find that, if an entrepreneur makes a connection with an interlocking partner in the same industry, it enhances their knowledge absorption, thereby providing a positive moderating effect, while investing in a country with a strong degree of openness weakens the effect of knowledge application, and thus plays a negative moderating role. This study makes practical and theoretical contributions by exploring specific vicarious learning means for entrepreneurs to enhance their firm’s international competitiveness, and also identifying three different learning processes.